A Taxonomy for Communication Challenges Faced by Multicultural Teams in Construction Projects - Jessica Justin SUNDEEP; Amir Hossein GHAPANCHI (Communications of International Proceedings, 2022)
The globalisation of construction projects has underlined the relevance of multiculturalism and the challenges it creates. This paper explores the research question “What are the Communication challenges faced by multicultural teams in construction projects?”. A qualitative research approach and case study method is used in this paper. The analysis of the data used to answer the research question led to providing a taxonomy for various challenges faced by Multicultural Teams in Construction Projects. Implications for practitioners are provided at the end of this paper.
Keywords: Multicultural teams; Construction Projects; Communication Challenges; Intercultural; Global Project Teams.